2013
DOI: 10.1155/2013/706354
|View full text |Cite
|
Sign up to set email alerts
|

Facile and Sensitive Epifluorescent Silica Nanoparticles for the Rapid Screening of EHEC

Abstract: This study was to develop antibodies conjugated fluorescent dye-doped silica nanoparticles (FDS-NPs) aiming to increase signals for the rapid detection of Escherichia coli O157:H7 with glass slide method. The FDS-NPs were produced with microemulsion/solgel techniques resulting in spherical in shape with 47 ± 6 nm in diameter. The particles showed high intensity and stable orange color Rubpy luminescent dye. The XRD spectrum showed a broad diffraction peak in the range of 18-30 ∘ (centered at 22 ∘) indicating a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…This finding was corresponding well with that of Gunasekaran et al [25], Tansub et al [17], and Tuitemwong et al [18] who suggested that wave numbers 3500-3220 cm −1 indicated amine group N-H stretching and 1850-1550 cm −1 for carboxyl group C=O on the FDS-NP surfaces.…”
Section: Characteristics Of Fds-npssupporting
confidence: 91%
See 3 more Smart Citations
“…This finding was corresponding well with that of Gunasekaran et al [25], Tansub et al [17], and Tuitemwong et al [18] who suggested that wave numbers 3500-3220 cm −1 indicated amine group N-H stretching and 1850-1550 cm −1 for carboxyl group C=O on the FDS-NP surfaces.…”
Section: Characteristics Of Fds-npssupporting
confidence: 91%
“…The size of FDS-NPs of approximately 30-60 nm was consistent with that previously reported [14,15,17,18]. Thepwiwatjit et al [14] reported the FDS-NPs with relatively narrow size of 29-43 nm.…”
Section: Characteristics Of Fds-npssupporting
confidence: 89%
See 2 more Smart Citations
“…Use of fluorescence nanoparticles in combination with magnetic beads capable of capturing and concentrating target specimens in the sampling process has been established to overcome the limitation of fluorescence intensity [ 9 12 ]. Fluorescent nanoparticles (about 10–20 μ m diameter in range) including semiconductor nanoparticles, quantum dots, metal nanoparticles, silica nanoparticles, and polymer nanoparticles have been focused for research and development.…”
Section: Introductionmentioning
confidence: 99%